LITERARY DIALOGUE REFLECTIONS ON THE NOBLE QURAN (SURAT TAHA AS A MODEL) - Munadhil Adil Kasim; Emad Kadhim Katea; Farah Sami (American Journals Publishing, 2025)
The Holy Quran is replete with dialogue, employing it as a fundamental method for persuasion and communication among individuals of many races, beliefs, thoughts, and perceptions regarding Allah, existence, the unseen, and the hereafter. This encouraged me to halt and contemplate the principles, etiquette, and prerequisites of debate in the Holy Quran, particularly the discourse among contradictory perspectives. The Almighty proclaims: "Say, "You will not be asked about what we committed, and we will not be asked about what you do." What captivated my attention was his portrayal of the injustices against Muslims as criminal acts: {Say, "You will not be asked about what we committed}, whereas he depicted the injustices against non-believers in a neutral manner, refraining from a negative stance, stating: {and we will not be asked about what you do}. The two descriptions stem from the prior assumption in the preceding verse, which places the interlocutors on equal footing without preconceived biases {And indeed, we or you are either upon guidance or in clear error}. They undoubtedly provide the most suitable foundation for a serious and constructive dialogue aimed at persuasion and subsequent reform. This topic pertains to the re-invocation of the Holy Quran , which has significantly shaped this nation, leading to its identification as the nation of the Quran , and has maintained a notable influence in its existence. An objector can enquire: How is that possible when he recites continuously, both day and night? This does not alter the truth in any way. It is not merely a request for additional recitation, but rather an appeal for contemplation, comprehension, and action beyond that. It is evident that the interpretation of the Holy Quran has significantly changed over time. In ancient times, if the nation regarded the Holy Quran as its foundational point, purpose, and focal concern—serving as both the starting point and the reference for measuring and evaluating the cultures of peoples and civilisations that embraced it—our contemporary circumstances have undergone significant transformation. This scenario necessitates a thorough examination of the fundamental question: "How do we engage with the Quran ?" Despite the problem's extensive and multifaceted nature, the assertion that it may be addressed in any study endeavour is illusory. Nonetheless, this does not preclude their contribution to the provocation, which we hope will not be in vain. Consequently, adhering to the principle of "what is not perceived does not depart," I selected the domain of dialogue in the Holy Quran , aspiring that our contributions may foster a broader appeal for enhanced communication, potentially mitigating the severity of the conflicts observed among individuals, nations, and civilisations, along with their repercussions. I intentionally selected the title "The Culture of Dialogue in the Holy Quran " to demonstrate that dialogue is not a peripheral or minor element of the Quran ic text, but rather a significant characteristic of it. The Quran advocated for discussion, delineated its characteristics, and cautioned against its drawbacks. Integrating all these elements, we arrive at what may be termed a "culture of dialogue in the Holy Quran".
Keywords: Reflections, Literary dialogue, The Holy Quran, Surah Taha